KONTRIBUSI KEKUATAN OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN DENGAN KETERAMPILAN SMASH FOREHAND DALAM PERMAINAN TENIS MEJA CLUB KITOGALO - Yuni Astuti Dwi Ningsih; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted with the aim to determine the contribution of shoulder arm muscle strength and hand eye coordination with smash forehand skills in the club kitogalo. The problems found in this study are the strength of the shoulder arm muscles and eye hand coordination are still inaccurate and less directional, it is seen when an athlete performs a table tennis forehand smash, still looks less maximal and directed as a result the ball is easily blocked by the opponent. This research was carried at club kitogalo. This research was conducted from February to July 2020. The sampling technique used in this study was total sampling, in which a total population of 6 people was selected as a sample. Based on the results of the study that the author has described in the previous chapter, the following conclusions can be drawn: